Implementasi Model Pembelajaran Kooperatif Tipe STAD Dalam Meningkatkan Hasil Belajar Siswa Pendidikan Dasar - Muhammad Abdullah; Yakin Akbar Asikin; Irawati Sabanja (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to determine the implementation of the STAD type cooperative learning model in improving the learning outcomes of basic education students. This study uses classroom action research with 15 students as subjects of Class IV SD Negeri Sebanjar, Alor Village, Northwest Alor District, East Nusa Tenggara, consisting of 7 males and 8 females. This research was carried out in two cycles, and each cycle was carried out in 3 meetings including tests at the end of each cycle. Data collection was carried out using learning outcomes tests at the end of each cycle, observation sheets for teacher and student activities carried out during the learning process and student response questionnaires. The collected data was then analyzed using descriptive analysis techniques. The results of this classroom action research analysis found that the implementation of the STAD Type Cooperative learning model for two cycles has been able to improve the learning outcomes of Class IV students at SD Negeri Sebanjar, Alor Village, Alor Barat Laut Subdistrict, East Nusa Tenggara, which is reflected in several aspects, including: (a) the increase in student learning outcomes, this can be seen from the increase in the average total percentage of learning outcomes, namely in the first cycle by 60% and in the fairly good category, increasing in the second cycle to 86.7% and in the very category good; (b) an increase in the activity of teachers and students in the learning process in accordance with the results of observations made during the study. for teacher activity, namely in the first cycle the average percentage of teacher activity was 77.8% and in the second cycle it increased to 90.3%. for student activities, namely in the first cycle the average percentage of student activity was 74% and in the second cycle it increased to 91.7%; and (c) students gave a positive response to the implementation of the STAD type cooperative learning model with an average total percentage of 100%.